Identification and Characterization of a Hemolysin Gene Cluster in Vibrio anguillarum - Jessica L. Rock; David R. Nelson (2006)
ABSTRACT Vibrio anguillarum is a causative agent of vibriosis in fish. Hemolytic activity has been suggested as a virulence factor by contributing to hemorrhagic septicemia and diarrhea. In order to identify and characterize the hemolysin genes and examine the role of hemolytic activity in virulence, a mini-Tn 10 Kan mutagenesis clone bank of V. anguillarum was screened. While no hemolysin-negative strains were observed, several mutants with two- to threefold-increased hemolytic activity were found. The region containing the insertion mutation was cloned, sequenced, and found to contain the V. anguillarum hemolysin ( vah1 ) and two other open reading frames, coding for a putative lactonizing lipase ( llpA ) and a putative phospholipase ( plp ). The mini-Tn 10 Kan was inserted into plp . Site-directed mutagenesis of each gene revealed that mutations in vah1 and llpA did not affect hemolytic activity, but insertions into plp caused a two- to threefold increase in hemolysis. Double mutations in plp and either vah1 or llpA resulted in wild-type hemolytic activity. Complementation of plp restored hemolytic activity to wild-type levels. Spectrophotometric determination of hemolysin specific activity revealed that activity on a per cell basis peaked during the first 2 h of growth in LB20. Real-time quantitative reverse transcriptase PCR used to quantitate transcription of the hemolysin genes plp and vah1 in V. anguillarum wild-type strains M93Sm and NB10 revealed that transcription of plp and vah1 peaked at 2 h of growth in LB20. Additionally, expression of vah1 measured in the plp mutant strain, JL01, during the first 2 h of growth was >8 times higher than that in M93Sm. Mutations in plp and llpA did not affect virulence of V. anguillarum . The mutation in vah1 attenuated V. anguillarum virulence in fish. These data show that several genes are responsible for hemolytic activity in V. anguillarum . At least three genes ( plp , llpA , and vah1 ) are responsible for one hemolytic activity. The data also suggest that plp acts as a negative regulator of vah1 and llpA .